Assessment of Liver Remnant Using ICG Clearance Intraoperatively during Vascular Exclusion: Early Experience with the ALIIVE Technique. (27th May 2015) - Lau, Lawrence; Christophi, Christopher; Nikfarjam, Mehrdad; Starkey, Graham; Goodwin, Mark; Weinberg, Laurence; Ho, Loretta; Muralidharan, Vijayaragavan
Abstract : Background . The most significant risk following major hepatectomy is postoperative liver insufficiency. Current preoperative assessment of the future liver remnant relies upon assumptions which may not be valid in the setting of advanced resection strategies. This paper reports the feasibility of the ALIIVE technique which assesses the liver remnant with ICG clearance intraoperatively during vascular exclusion. Methods . 10 patients undergoing planned major liver resection (hemihepatectomy or greater) were recruited. Routine preoperative assessment included CT and standardized volumetry. ICG clearance was measured noninvasively using a finger spectrophotometer at various time points including following parenchymal transection during inflow and outflow occlusion before vascular division, the ALIIVE step. Results . There were one case of mortality and three cases of posthepatectomy liver failure. The patient who died had the lowest ALIIVE ICG clearance (7.1%/min versus 14.4 ± 4.9). Routine preoperative CT and standardized volumetry did not predict outcome. Discussion/Conclusion . The novel ALIIVE technique is feasible and assesses actual future liver remnant function before the point of no return during major hepatectomy. This technique may be useful as a check step to offer a margin of safety to prevent posthepatectomy liver failure and death. Further confirmatory studies are required to determine a safety cutoff level.